Pengaruh Edukasi Video Terhadap Pengetahuan Dan Sikap Remaja Tentang Pernikahan Usia Dini Di SMP Islam Pagimana, Kabupaten Banggai Tahun 2024 - Rismawati, Rismawati; Yulis, Dian Meiliani; Yuliana, Besse; Herman, Sriyana; Rusli, Rusli (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2024)
This study aims to analyze the effect of video-based education about early marriage on the knowledge and attitudes of students at SMP Islam Pagimana, Banggai Regency, Central Sulawesi. The design of this study is a pre-experimental study with a one-group Pretest-Posttest design. In this study, the researcher provided a group intervention that was initially measured through a test (Pretest), then after the intervention was given the group would be measured again using a Posttest. This research was conducted at SMP Islam Pagimana, Banggai Regency, Central Sulawesi in December 2024. The population in this study were all students of SMP Islam Pagimana, Banggai Regency in the 2023/2024 academic year with a total of 248 people. The sample used in this study was 71, but to anticipate dropouts, 10% was added to a total of 78 people. The respondents used in this study were classes VII, VIII, and X. Samples from each class were taken using the spin or random method because the number of students in each class was different. Data collection from the research results used a questionnaire. Data analysis used was univariate and bivariate analysis. The results of the study showed that there was an increase in knowledge before and after counseling by 21.7%. There was an increase in attitudes before and after counseling by 56.4%. It is known that there is a significant difference in the average increase in knowledge about early marriage before and after being given educational videos.